MALDI-TOF MASS SPECTROMETRY IN MICROORGANISM IDENTIFICATION - E. A. Demidov; K. V. Starostin; V. M. Popik; S. E. Peltek (Вавиловский журнал генетики и селекции)
Identification of microorganisms from their protein profiles, or direct protein profiling, has been extensively used in the last decade. Being sufficiently accurate and specific, this method is fast and inexpensive. In this review, current notions of the potential of this method are considered and it is compared with other approaches to microorganism identification.